Awareness of Breastfeeding Among Nursing Students of Al-Tibri Medical College & Hospital (Medical Forum Monthly, 2021)
Objective: To provide the awareness of breastfeeding among nursing students.Study Design: Descriptive case study.Place and Duration of Study: This study was conducted at the Al-Tibri Medical College & Hospital, Al-Tibri School of nursing, Karachi between the duration of November 2020 to April 2021.Materials and Methods: A total of 42 responses were received including 30 male and 12 female nursing students. A survey of 28 close- and open ended questions was developed after extensive literature review.Results: Among 42 responses, majority of students were male 71% and 29% were female with mean age of 20.18 ± 0.13. The maximum numbers of our nursing students have basic knowledge of breastfeeding and were familiar about its benefits but less aware about the transmission of communicable diseases (such as HBV, HCV, HIV, and TB) through breast milk. Moreover there is need to emphasize the nursing curriculum to advance their knowledge against breastfeeding.Conclusion: These studies revealed that majority of the female nursing students were more aware about the breastfeeding and its benefits than male nursing students. There is no statistical association observed between the gender and awareness regarding breastfeeding